2014
DOI: 10.1016/j.medici.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Importance of alcohol-related expectations and emotional expressivity for prediction of motivation to refuse alcohol in alcohol-dependent patients

Abstract: Negative alcohol-related expectations, emotional impulse intensity and positive emotional expressiveness were significant even though quite weak triggers for alcohol-dependent patients' different level of motivation to refuse alcohol consumption. An assumption could be made that by changing these triggers it is possible to change addictive behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Results indicate that younger people understand the problem severity, that they adequately perceive consequences and damage that could face if they do not make a change. Accordingly, some studies suggest that older people could be in a phase of problem severity denial, which could cause them not to see negative consequences of alcohol in their daily functioning due to formed habits and attitudes [11]. This result is contrary to previous studies, according to which elderly people show higher total motivation for abstinence and therefore also higher recognition of problem [26,21,7].…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Results indicate that younger people understand the problem severity, that they adequately perceive consequences and damage that could face if they do not make a change. Accordingly, some studies suggest that older people could be in a phase of problem severity denial, which could cause them not to see negative consequences of alcohol in their daily functioning due to formed habits and attitudes [11]. This result is contrary to previous studies, according to which elderly people show higher total motivation for abstinence and therefore also higher recognition of problem [26,21,7].…”
Section: Discussionmentioning
confidence: 83%
“…Subjects' average age in this study was 49 years that could, according to some categorizations, be defined as a sample of predominantly older people. Some other authors have already warned that there are not universally defined age groups [7,11]. To sum up, this result could be also affected by gender, because other studies showed that older women have higher abstinece motivation [7].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations